Model Supervisi Transformatif-Humanistik Berbasis Nilai Kearifan Lokal Untuk Pengembangan Profesionalisme Guru Di Era Merdeka Belajar - Rifa'i Rifa'i; Rohmad Yasin; Nurotun Mumtahanah (Educational Research Center, 2026)
This study aims to develop a transformative-humanistic supervision model based on local wisdom values for teacher professional development in the Merdeka Belajar era. Islamic education supervision has shifted from a control-based approach toward a professional development model that is more humanistic, democratic, participatory, and reflective. This research uses a literature study method with a descriptive-qualitative approach through analysis of books and scholarly articles related to educational supervision, humanistic approaches, local wisdom, and Merdeka Belajar policy. The findings indicate that control-based supervision tends to suppress teacher agency, shape a defensive professional identity, and reduce pedagogical initiative. Conversely, dialogic and trust-based supervision strengthens teacher agency, shapes a reflective professional identity, and encourages pedagogical courage. The integration of Indonesian local wisdom values such as gotong royong (mutual cooperation) and musyawarah (deliberation) with modern supervision approaches creates a distinctive supervision model that is contextual and culturally relevant. The incorporation of local values such as gotong royong (mutual cooperation), musyawarah (deliberation), and tolerance in both intraclass activities and the Pancasila Student Profile strengthening projects contributes to contextual character development among students. This study concludes that the transformative-humanistic supervision model based on local wisdom values can effectively enhance teacher professionalism while maintaining cultural identity in the Merdeka Belajar era.